Peer relationships with attitudes towards sexual violence - Pangestuti, Restu; Fatimah, Fatimah; Paramita, Dyah Pradnya; Mulyaningsih, Sundari; Wulandari, Baiq Rina (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Based on Regulation Indonesian Minister of Health Number 25 of 2014, adolescents are peoples aged 8-10 years old but according to the National Population and Family Planning Board (BKKBN) adolescents are peoples with an age range of 10-24 years and unmarried.Proportion of first-time dating adolescents in Indonesia at the age of less than 15 years. Based on data from the Global School Heatlh Survey 2015, there are 3.3% of adolescents aged 15-19 years have AIDS, only 9.9% of teenage girls and 10.6% of teenage boys have comprehensive knowledge about HIV AIDS, and as many as 0.7% of teenage girls and 4.5% of teenage boys have had premarital sexual relations. Adolescents who understand about the signs of puberty and about reproductive health are still very lacking. Yogyakarta City is still poor in knowledge with various health problems, especially adolescent reproductive health. Sexual violence cases in the city of Yogyakarta rank 5th out of 34 provinces in Indonesia, with a total of 894 victims.Objectives: To determine the relationship between peers and attitudes towards sexual violence.Methods: We conducted analytical descriptive correlation method and study design cross sectional study. The independent variable in this study was peers and dependent variable in this study was attitudes towards sexual violence. Data analysis uses univariate analysis and bivariate analysis to analyze the relationship between two variables. The statistical analysis used in this study is the spearman rank test.Results: The results showed that there was a relationship between peers (p value 0.009) and showed a sufficient correlation (r = 0.174) which means there is a relationship with attitudes towards sexual violence.Conclusions: There was a significant relationship between peers and attitudes toward sexual violence.